2009
DOI: 10.1210/jc.2009-0226
|View full text |Cite
|
Sign up to set email alerts
|

Familial Frameshift SRY Mutation Inherited from a Mosaic Father with Testicular Dysgenesis Syndrome

Abstract: This observation of somatic and germinal mosaicism for a SRY mutation may explain the variable penetrance in some familial gonadal dysgenesis. Importantly, the present report is the first one describing the association of SRY mutation in a male with TDS. This suggests that mutations in a sex-determining gene may contribute to the pathogenesis of TDS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
18
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 17 publications
4
18
0
1
Order By: Relevance
“…This hypothesis seemed to be in line with the reports of synchronous trends in TGCC, sperm counts, cryptorchidism and hypospadias [37]. We [30] and others [29,38] have since been testing the hypothesis and found further evidence of a role of rare mutations in genes that control androgen action and Sertoli cell function in DSD patients with signs and symptoms of TDS. However, most patients with TGCC have much less obvious manifestations of DSD, which, in addition to the tumour, include an increased risk of cryptorchidism and impaired spermatogenesis [19,39].…”
Section: Testicular Dysgenesis Syndromesupporting
confidence: 89%
See 1 more Smart Citation
“…This hypothesis seemed to be in line with the reports of synchronous trends in TGCC, sperm counts, cryptorchidism and hypospadias [37]. We [30] and others [29,38] have since been testing the hypothesis and found further evidence of a role of rare mutations in genes that control androgen action and Sertoli cell function in DSD patients with signs and symptoms of TDS. However, most patients with TGCC have much less obvious manifestations of DSD, which, in addition to the tumour, include an increased risk of cryptorchidism and impaired spermatogenesis [19,39].…”
Section: Testicular Dysgenesis Syndromesupporting
confidence: 89%
“…Although a possible link between hypospadias and TGCC has been questioned [25], more recent studies have shown a clear association, which is however weaker than that between TGCC and cryptorchidism [26,27]. In addition, an association between TGCC and severe forms of hypospadias, as seen in patients with disorders of sex development (DSD), has been known since the early studies of Scully [28] and recently confirmed in patients with heterogeneous genetic phenotypes, such as mutations in SRY [29] or androgen receptor gene [17,30]. However, in the vast majority of patients with TGCC, no mutations have been found.…”
Section: Testis Cancer and Other Male Reproductive Problemsmentioning
confidence: 99%
“…The p.Ile738Met mutation described here is a rare example of a clear genetic component in the pathogenesis of TDS. Recently, a novel SRY frame-shift mutation found in a mosaic state in a patient with testicular cancer, cryptorchidism, hypospadias, and oligoasthenozoospermia was described (19). Thus, the full TDS phenotype including TGCT has now been observed in individuals with mutations affecting 2 different genes involved in virilization and testicular development.…”
Section: Figurementioning
confidence: 99%
“…However, considering the limited sensitivity of STS-PCR assays and the small number of individuals examined, further studies are required to clarify the association between AZF-linked CNVs and hypospadias. In addition, although mosaic loss-of-function mutations of SRY have been associated with both SF and hypospadias [Isidor et al, 2009;Shahid et al, 2010], CNVs of the SRY locus have rarely been analyzed in hypospadias patients. Here, we performed MLPA analysis to evaluate the frequency of CNVs of the AZF region and SRY in 89 Japanese children with hypospadias.…”
Section: Y Chromosomal Cnvs and Hypospadiasmentioning
confidence: 99%